Pulmonary function changes and its influencing factors after preoperative brace treatment in patients with adolescent idiopathic scoliosis: A retrospective case–control study. Issue 43 (October 2016) - Ran, Bo; Fan, Yuxin; Yuan, Feng; Guo, Kaijin; Zhu, Xiaodong
Abstract: Background: The aim of the study was to retrospectively investigate the changes in pulmonary function and its influencing factors in patients with adolescent idiopathic scoliosis (AIS) undergoing preoperative brace treatment or not. Methods: Total 237 AIS patients (43 boys, 194 girls) who underwent operations and had a complete record of pulmonary function tests were enrolled and were divided into preoperative brace treatment group (brace treatment group, n = 60) and without preoperative brace treatment group (control group, n = 177). The pulmonary function parameters were compared between the 2 groups. Multiple linear regression analysis was performed to explore whether the variables, including age at operation, height, coronal Cobb's angle of main curve, number of involved vertebrae, sagittal Cobb's angle of thoracic curve, brace treatment time per day and brace treatment duration, influenced pulmonary function in the brace treatment group. Results: No significant differences were observed in both predicted and actually measured value of forced vital capacity (FVC) and predicted value of forced expiratory volume in 1 s (FEV1) between 2 groups ( P > 0.05), but actually measured FEV1, the percentage of actually measured and predicted value of FVC (FVC%) and FEV1 (FEV1%) were significantly lower in the brace treatment group than those in the control group ( P < 0.05). Importantly, the above changes in actually measured FEV1 and FEV1% were obvious in AIS patients presented with a main thoracic curve ( P < 0.05), but not in patients with a primary thoracolumbar/lumbar curve. Multiple linear regression analysis indicated that only the sagittal Cobb's angle of the thoracic curve was positively, but preoperative brace treatment duration was negatively associated with both the FVC% and FEV1% ( P < 0.05). Conclusion: Preoperative brace treatment may deteriorate pulmonary function in AIS patients with thoracic curve. The small sagittal Cobb angle and longer brace treatment duration may be risk factors for reduced pulmonary function.